(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Let G be a graph. Then a subset C of vertices of G is called a vertex cover hop dominating if C is both a vertex cover and a hop dominating of G. The vertex cover hop domination number of G, denoted by γ_vch(G), is the minimum cardinality among all vertex cover hop dominating sets in G. In this paper, we initiate the study of vertex cover hop domination in a graph and we determine its relations with other parameters in graph theory. We characterize the vertex cover hop dominating sets in some special graphs, join, and corona of two graphs and we finally obtain the exact values or bounds of the parameters of these graphs.